2003
DOI: 10.1097/00001721-200312000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Impaired spontaneous thrombolytic activity in elderly and in habitual smokers, as measured by a new global thrombosis test

Abstract: We used a new test (the Görög Thrombosis Test) for assessing the effect of aging, smoking and exercise habits on the overall thrombotic status including platelet reactivity and spontaneous thrombolytic activity of 30 healthy young males (mean, 21.1 +/- 0.4 years) and 34 elderly males (64.5 +/- 1.1 years). The occlusion time (OT) and the lysis time (LT) were measured from a single native blood sample. The OT is an index of platelet activation and subsequent occlusive thrombus formation by high shear stress, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…The shear-induced thrombosis and thrombolysis tests were performed on non-anticoagulated blood (haemostatometer, thrombotic status analyser, and GTT). The thrombotic state was influenced by age (46), smoking (46)(47)(48), gender (47), and race (49). These findings corroborate the results of clinical studies indicating that physical exercise or sports helped to prevent a prothrombotic state and increased an individual's quality of life (3,38,41,50).…”
Section: Effect Of Long-term Exercisesupporting
confidence: 77%
“…The shear-induced thrombosis and thrombolysis tests were performed on non-anticoagulated blood (haemostatometer, thrombotic status analyser, and GTT). The thrombotic state was influenced by age (46), smoking (46)(47)(48), gender (47), and race (49). These findings corroborate the results of clinical studies indicating that physical exercise or sports helped to prevent a prothrombotic state and increased an individual's quality of life (3,38,41,50).…”
Section: Effect Of Long-term Exercisesupporting
confidence: 77%
“…The latter occurs in less than an hour, a time frame acceptable both in the laboratory and in clinical settings. In volunteers of different age groups, spontaneous thrombolysis was significantly impaired in habitual smokers [71], in elderly males but not in females. It was suggested that this could be an explanation for the well-established gender differences in risk of acute coronary syndromes [72].…”
Section: Global Assessment Of Spontaneous Thrombolytic Activitymentioning
confidence: 88%
“…Platelet aggregation induced by shear forces is, however, more similar to the pathological process of arterial thrombosis than the agonist-induced plateletaggregation tests [12]. Furthermore, an in vitro test performed from native, non-anticoagulated blood has much more relevance in vivo than those tests that use anticoagulated blood [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%